The effectiveness of adapted psychological interventions for people from ethnic minority groups: A systematic review and conceptual typology. (August 2021) - Arundell, Laura-Louise; Barnett, Phoebe; Buckman, Joshua E.J.; Saunders, Rob; Pilling, Stephen
Abstract: This review assessed the efficacy of adapted psychological interventions for Black and minority ethnic (BME) groups. A conceptual typology was developed based on adaptations reported in the literature, drawing on the common factors model, competence frameworks and distinctions between types of cultural adaptations. These distinctions were used to explore the efficacy of different adaptations in improving symptoms of a range of mental health problems for minority groups. Bibliographic searches of MEDLINE, Embase, PsycINFO, HMIC, ASSIA, CENTRAL, CDSR and CINAHL spanned the period from 1965 to December 2020. Adaptations to interventions were categorised: i) treatment specific: therapist-related, ii) treatment-specific: content-related and iii) organisation-specific. Meta-analyses of RCTs found a significant effect on symptom reduction when adapted interventions were compared to non-adapted active treatments ( K  = 30, Hedge's g  = -0.43 [95% CI: -0.61, -0.25], p  < .001). Studies often incorporated multiple adaptations, limiting the exploration of the comparative effectiveness of different adaptation types, although inclusion of organisation-specific adaptations may be associated with greater benefits. Future research, practitioner training and treatment and service development pertaining to adapted care for minority groups may benefit from adopting the conceptual typology described. Highlights: Ethnic minority groups benefit from adapted psychological interventions Identifying the most efficacious adaptation types is challenging Services might consider organisation-specific adaptations Consistency is needed in the definitions of cultural adaptations